Dos especies nuevas de hormigas de la tribu Attini de Costa Rica y México: Mycetosoritis vinsoni y Mycocepurus curvispinosus (Hymenoptera: Formicidae) - Mackay, William P (Revista de Biología Tropical, 1998)
I describe Mycetosoritis vinsoni from Loma Barbudal, Guanacaste Prov., Costa Rica, based on a holotype worker. It is most closely related to M. hartmanni, but can be easily separated as the hairs on the scapes are curved and appressed (straight and semierect in M. hartmanni), the median pronotal denticles are absent (present and well developed in M. hartmanni) and the petiolar teeth are poorly developed (well developed in M. hartmanni). Mycocepurus curvispinosus is described based on five workers from Costa Rica, Guanacaste Prov., Loma Barbudal and Mexico, Chiapas, 24 km southeast of Cintalpa. It can be easily recognized as the propodeal spines are thickened and bent upwards, and the mid pronotal denticles are absent. These two characters separate this new species from all others in the genus.